Responses of rhizosphere soil nutrients to phosphorus addition and arbuscular mycorrhizal fungi inoculation in karst plantations - Wang, Miaomiao; Hu, Yiran; Li, Qiuyun; He, Xinxi (Frontiers in Forests and Global Change, 2025)
IntroductionCompared with natural restoration, the recovery of soil ecological function in plantations is relatively lagging. Exogenous phosphorus (P) input and arbuscular mycorrhizal fungi (AMF) inoculation could eliminate or alleviate nutrient limitation in soil for plants. However, the differences in AMF community structure associated with P addition and AMF inoculation and their effects on soil nutrients remain unclear. The rhizosphere is vital for plant productivity and soil ecosystem function.MethodsBased on in situ P addition (Ca(H2PO4)2 fertilizer) and AMF inoculation (Rhizophagus intraradices inoculant) treatments in plantations in typical karst areas in Hunan Province, China, stratified rhizosphere soil samples of 0–15 and 15–30 cm were collected to determine alkaliolytic nitrogen (AN), available phosphorus (AP), soil organic carbon (SOC) contents, and AMF community composition. The corresponding non-rhizosphere soil samples were collected with cutting rings to determine their physical properties.ResultsAfter P addition, AP contents in both the 0–15 and 15–30 cm layers increased significantly. In addition, AN contents in 0–15 and 15–30 cm layers and SOC content in the 0–15 cm layer increased, with no significant changes. After AMF inoculation, AP content in the 15–30 cm layer and SOC content in the 0–15 cm layer increased, with no significant changes. P addition and AMF inoculation increased AMF colonization intensity significantly in the roots, in turn altering the relative abundance in the AMF community and increasing Chao1 richness, Pielou’s evenness, and Simpson’s and Shannon’s diversity indices. Compared with the control, the relationships between soil nutrients and other properties varied after P addition and AMF inoculation. The effects of AMF community relative abundance and diversity on soil nutrients changed after P addition and AMF inoculation, with explanations for soil nutrient variations of the former both decreasing and the latter both increasing.DiscussionThe results clarify the responses of rhizosphere soil properties to exogenous P input and AMF inoculation in plantations in karst areas. This can facilitate soil ecological function restoration and sustainable recovery of fragile ecosystems.